2022
DOI: 10.15585/mmwr.mm7102e1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of BNT162b2 (Pfizer-BioNTech) mRNA Vaccination Against Multisystem Inflammatory Syndrome in Children Among Persons Aged 12–18 Years — United States, July–December 2021

Abstract: On January 7, 2022, this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr).Multisystem inflammatory syndrome in children (MIS-C) is a severe postinfectious hyperinflammatory condition, which generally occurs 2-6 weeks after a typically mild or asymptomatic infection with SARS-CoV-2, the virus that causes COVID-19 (1-3). In the United States, the BNT162b2 (Pfizer-BioNTech) COVID-19 vaccine is currently authorized for use in children and adolescents aged 5-15 years under a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
193
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 242 publications
(236 citation statements)
references
References 7 publications
(17 reference statements)
8
193
0
2
Order By: Relevance
“…Multisystem inflammatory syndrome in adults was not reported in clinical trials of COVID-19 vaccines used in the USA, and MIS-C was not observed in the 46 000 individuals aged 16 years or older who participated in safety clinical trials for BNT162b2. 10 , 25 Globally, MIS-C in individuals who had received a COVID-19 vaccine has been described in detail in the literature for eight individuals younger than 21 years, 22 , 26 , 27 , 28 , 29 , 30 , 31 excluding aggregate counts from larger analyses assessing the effect of vaccination on preventing MIS-C. 32 , 33 From the USA, two reports included three cases that are also in our surveillance results, 22 , 26 and one report described a 14-year-old child with evidence of previous SARS-CoV-2 infection (positive anti-nucleocapsid antibody test) with MIS-C onset 2 months after a second dose with BNT162b2. 31 From outside the USA, we found reports of two individuals without evidence of previous or recent SARS-CoV-2 infection and who tested negative for anti-nucleocapsid antibodies: from Denmark, a 17-year-old with MIS-C onset 5 days after dose two of BNT162b2; 28 and from Turkey, a 12-year-old with onset 27 days after dose one of BNT162b2.…”
Section: Discussionmentioning
confidence: 99%
“…Multisystem inflammatory syndrome in adults was not reported in clinical trials of COVID-19 vaccines used in the USA, and MIS-C was not observed in the 46 000 individuals aged 16 years or older who participated in safety clinical trials for BNT162b2. 10 , 25 Globally, MIS-C in individuals who had received a COVID-19 vaccine has been described in detail in the literature for eight individuals younger than 21 years, 22 , 26 , 27 , 28 , 29 , 30 , 31 excluding aggregate counts from larger analyses assessing the effect of vaccination on preventing MIS-C. 32 , 33 From the USA, two reports included three cases that are also in our surveillance results, 22 , 26 and one report described a 14-year-old child with evidence of previous SARS-CoV-2 infection (positive anti-nucleocapsid antibody test) with MIS-C onset 2 months after a second dose with BNT162b2. 31 From outside the USA, we found reports of two individuals without evidence of previous or recent SARS-CoV-2 infection and who tested negative for anti-nucleocapsid antibodies: from Denmark, a 17-year-old with MIS-C onset 5 days after dose two of BNT162b2; 28 and from Turkey, a 12-year-old with onset 27 days after dose one of BNT162b2.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent report estimated that two doses of BNT162b2 were 91% effective against the development of MIS-C among adolescents aged 12–18 years when the delta (B.1.617.2) variant was predominant. 9 Together with the report by Yousaf and colleagues, these data offer hope that vaccination will reduce morbidity and mortality due to MIS-C.…”
mentioning
confidence: 83%
“…First, a third booster vaccination is recommended after two doses of vaccine to restore protection against SARS-CoV-2 infection. Second, children need to be vaccinated to protect them from severe COVID-19 and MIS-C, 9 and to control the spread of COVID-19 in the community. Third, the REACT-1 study clearly shows the importance of tracing infections to understand the epidemiological evolution of the pandemic, www.thelancet.com/respiratory Published online January 24, 2022 https://doi.org/10.1016/S2213-2600(22)00016-9 which is even more important now that we are facing the challenge of the omicron variant.…”
Section: Tracing and Vaccinating: How To React To Covid-19 Pandemicmentioning
confidence: 99%